Predicting Patient Satisfaction in Dental Healthcare: The Influence of Service Quality, Price, and Location - Cahyadi, Yohanes Tri; Karnawati, Tin Agustina; Widodo, Teguh (Economics and Digital Business Review, 2026)
Healthcare service quality plays a vital role in addressing competition among healthcare providers. For dental clinics, maintaining sustainability requires managerial strategies oriented toward enhancing patient satisfaction. This study aims to examine the effects of service quality, price, and location on patient satisfaction at ANT Dental Care. The population comprised all patients who had received treatment at ANT Dental Care. Using a purposive sampling technique, questionnaires were distributed to 193 active patients during the research period. The data were analyzed quantitatively using multiple linear regression, including validity and reliability testing, classical assumption testing (normality, multicollinearity, and heteroscedasticity), and hypothesis testing through the coefficient of determination (R²), t-test (partial), and F-test (simultaneous). The results reveal that service quality, price, and location each have a positive and significant effect on patient satisfaction. Furthermore, simultaneously, service quality, price, and location significantly influence patient satisfaction at ANT Dental Care, as indicated by the F-test significance value below 0.05.